Treatment and outcome of a boy with lgG4-related hypophysitis caused by SARS-CoV-2 re-infection - Li, Hanming; Leong, Iatlun; He, Jianyu (Frontiers in Endocrinology, 2025)
RationaleSARS-CoV-2 infection can directly and indirectly affect the nervous system, including the hypothalamus and pituitary, and potentially cause IgG4-related hypophysitis.Patient concernsA 4-year-old Chinese boy presented with arginine vasopressin deficiency (AVP-D, previously called ‘central diabetes insipidus’) and significant growth retardation. MRI indicated thickening of the pituitary stalk and alterations in the posterior pituitary.DiagnosisThe boy experienced polydipsia, polyuria, and enuresis 4 months after infection by SARS-CoV-2 and 2 months prior to presentation in June 2023. The diagnosis was IgG4-related hypophysitis, AVP-D, and growth hormone deficiency. Treatment with glucocorticoids and desmopressin led to significant resolution of symptoms and normalization of pituitary morphology. However, a second SARS-CoV-2 infection was followed by recurrence of polydipsia, polyuria, and thickening of the pituitary stalk. This recurrence led to a final diagnosis of IgG4-related hypophysitis caused by SARS-CoV-2 infection.InterventionsGlucocorticoids and desmopressin alleviated the AVP-D. Growth hormone and a diet and exercise plan were recommended to manage his short stature. We plan to conduct a functional assessment of the gonadal axis after he is 6 years old.OutcomesAfter 18 months, the polydipsia and polyuria were controlled, and an MRI showed significant thinning of the pituitary stalk. This is the first reported case of lgG4-related hypophysitis in a Chinese boy infected with SARS-CoV-2.LessonsWe successfully controlled clinical symptoms, but further follow-up observations are needed to assess recovery. Although the role of SARS-CoV-2 infection in this patient’s condition is only suggestive, other reports have described a relationship between SARS-CoV-2 infection and lgG4-related hypophysitis.